Facilitators and barriers to the uptake of COVID-19 vaccine precaution dose among adult population: qualitative analysis across six different states of India - Godbole, Sheela; Diwan, Vishal; Das, Saibal; Reddy, Mahendra M.; Kalyanasundaram, Madhanraj; Rajendran, Dilipkumar; Biswas, Dipankar; Mamulwar, Megha; Tiwari, Rajnarayan R.; Majumder, Joydeep; Mishra, Ayush; Muthusamy, Santhosh Kumar; et al. (Frontiers in Public Health, 2024)
India launched the COVID-19 vaccination drive on 16January 2021 by vaccinating the adult population. Even though, the uptake of the primary doses remained optimal, irrespective of different interventions by the Government of India, the uptake of the precaution dose remained poor. In this context, the Ministry of Health & Family Welfare wanted to understand the facilitators and Barriers for precaution dose uptake among adults so that future immunization campaigns could address these issues. Hence, an exploratory qualitative study was conducted to assess the facilitators and barriers for COVID-19 precaution dose uptake at community level across 6 different states. From each of the states, two districts with the highest and lowest rates of COVID-19 vaccine precaution dose uptake were selected. In each of these districts, 2 block Primary Healthcare Centres (PHCs), one with high and one with low uptake were identified. Within these block PHCs, a PHC field area with high and low precaution dose uptakes was identified. At these sites a minimum of four IDIs, four FGDs and KIIs were conducted. The data was audio recorded, transcribed, translated and analysed using framework approach. Rise in COVID-19 cases, cost of hospitalization and loss of productive days resulted in vaccine uptake. The fear of non-availability of COVID-19 vaccines latter on also prompted people for vaccine uptake. While the barriers were, poor accessibility to vaccination centers, long hours of travel, poor road connectivity and lack of transportation facilities. The most prominent barriers across all study sites was that a sense of pandemic fatigue and complacency had developed both among the providers and beneficiaries. Other barriers include differences in vaccination schedules and longer duration between the primary doses of some vaccines. Even though media played an important role in disseminating information in the beginning of the campaign, it was soon followed by circulation of both misinformation and disinformation. The study identified that dissemination of accurate information and community involvement at each stage of planning and implementation are crucial for the success of any campaign. These lessons learnt must be applied in future vaccination campaigns and while framing public health policies.